Improving Students’ Speaking Skills Through Sociodramatic Play At The Second Grade Students Of Sma Negeri 2 Mamuju - Muhammad Ybnu T (Journal of Research and Multidisciplinary, 2021)
This study aims at finding out the effectiveness of sociodramatic play in improving the students’ speaking skills. This study is a quantitative research with Classroom Action Research (CAR) model. The respondents of the study were the second grade students of SMAN 2 Mamuju. The sample was taken through purposive sampling technique. Data were collected through speaking test and questionnaire. In this study, post- test was conducted in three cycles. The results of the study show that students had made some progress during the learning process. In pre-test, most of the students were having poor speaking skills with as many as 53% participants were in this category. However, there were significant improvements toward students’ speaking skills with no more students with both very poor and poor speaking skills in third cycle. From the result of the tests, it can be concluded that sociodramatic play is quite useful to improve students’ speaking skill. In addition, most of students feel interested and enjoy the learning process through sociodramatic play in speaking class